2011
DOI: 10.1007/s10693-011-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Déjà Vu All Over Again: The Causes of U.S. Commercial Bank Failures This Time Around

Abstract: Abstract:In this study, we analyze why commercial banks failed during the recent financial crisis. We find that traditional proxies for the CAMELS components, as well as measures of commercial real estate investments, do an excellent job in explaining the failures of banks that were closed during 2009, just as they did in the previous banking crisis of 1985 -1992. Surprisingly, we do not find that residential mortgage-backed securities played a significant role in determining which banks failed and which banks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
310
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 390 publications
(364 citation statements)
references
References 18 publications
32
310
1
1
Order By: Relevance
“…Blasko and Sinkey (2006) notice that real estate banks are riskier since they tend to be more capital constrained and they keep higher ratios of fixed-rate loans to total assets. Furthermore, Cole and White (2012) conclude that the basic drivers of bank financial performance and failure during the financial crisis are concentrations of commercial real estate loans.…”
Section: Riskmentioning
confidence: 98%
“…Blasko and Sinkey (2006) notice that real estate banks are riskier since they tend to be more capital constrained and they keep higher ratios of fixed-rate loans to total assets. Furthermore, Cole and White (2012) conclude that the basic drivers of bank financial performance and failure during the financial crisis are concentrations of commercial real estate loans.…”
Section: Riskmentioning
confidence: 98%
“…Fayman and He (2011) present evidence that the addition of a prepayment risk variable to regression models can improve their ability to explain bank performance measures, probably through its effect on return on loans, return on equity, and the ratio of real estate loans to total loans. Cole and White (2012) demonstrate that the traditional CAMELS proxies and measures of commercial real estate investments explain the failure of US banks in 2009, but that residential mortgage-backed securities do not.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Cole and White (2012) analyzed Call Report data from 2004 to 2008 in order to determine the factors that led to bank failures in 2009. They found that commercial real estate lending, particularly in the area of construction and development, is a strong early predictor of bank failure in this period.…”
Section: Literaturementioning
confidence: 99%